Design of fractional delay repetitive control with a dead-beat compensator for a grid-tied converter under distorted grid voltage conditions. (May 2020) - Straś, Andrzej; Ufnalski, Bartłomiej; Michalczuk, Marek; Gałecki, Andrzej; Grzesiak, Lech
Abstract: The paper presents the design of a current control system of a grid-tied converter which provides high dynamic in transients states and symmetrical sinusoidal currents under distorted and asymmetrical grid voltage conditions. The current control loop contains a dead-beat compensator and a plug-in fractional delay repetitive controller. The whole control system is designed with regard to signal processing delay present in the control loop. The tuning procedure of the repetitive control uses particle swarm optimization to determine the optimal gain, phase lead and filter parameter. The resulting control system with optimal parameters is applied on the digital signal controller and verified experimentally on the laboratory test bench, which is the main contribution of the paper. Highlights: Design of a current control system for a grid-tied converter under distorted and asymmetrical grid voltage is shown. Current control loop contains a dead-beat compensator and fractional delay repetitive controller. The overall control system is designed with regard to signal processing delay present in the control loop. Particle swarm optimization is used to determine parameters of fractional delay repetitive controller.